Predictive factors for referral to a peer support worker in psychosocial rehabilitation centers - Monnier, Romain; Plasse, Julien; Haesebaert, Frédéric; Gouache, Benjamin; Legros-Lafarge, Emilie; Guillard-Bouhet, Nathalie; Bralet, Marie-Cécile; Franck, Nicolas; Khattech, Dora; Barbalat, Guillaume; Giraudet, Céline (Frontiers in Psychiatry, 2025)
IntroductionPeer support workers are individuals with personal lived experience of mental health conditions, addictions, or neurodevelopmental disorders, and can be employed as professionals within mental health services. This study aims to identify predictive factors for patient referral to peer support intervention in psychosocial rehabilitation services.MethodsUsing data from the French REHABase cohort, we compared variables between patients referred (n=134) and not referred (n=242) to peer support intervention. We evaluated an expert-based model (clinician-selected variables) against a machine-based model (algorithm-selected variables) for predictive accuracy.ResultsThe machine-based model outperformed the expert-based model in the full dataset (AUC = 0.78 vs 0.71). However, the predictive performance of both models substantially declined after cross-validation, yielding modest AUC values (0.60 and 0.59), which constitutes a key limitation of the study.DiscussionNeurodevelopmental disorder diagnosis, social isolation, and low treatment adherence predicted peer support referral. Poor model performance may be due to unmeasured factors like patient motivation or clinicians’ perceptions of peer support workers.